Methods to increase the efficiency of rajphos (jamarkhotra rockphosphate) in the black soils of Palakkad district for rice - Vyas N G (Department of Soil Science and Agriculture, College of Agriculture, 2002)
There has been considerable interest in studying the efficiency of rockphosphate for direct application to the soil in the rice farming situations of Kerala, particularly tapping the iron - to - magnet type of relationship between rockphosphate and acid soils. However no work has been done in the neutral to alkaline soils of Kerala located in the Chittoor Taluk of Palakkad District to utilize the potential of rockphosphate. These soils are inherently poor In phosphorus and the situation 1S furthur complicated by the high P fixation capacity. Problems of fixation of soluble P can be alleviated to some extent by the use of less soluble forms like rockphosphate in conjunction with acid forming amendments like iron pyrites. sulphuric acid and P solubilising micro organisms. A study was undertaken to investigate the effect of direct application of rockphosphate in combination with amendments for rice in the Department of Soil Science and Agricultural Chemistry at the College of Agriculture, Vellayani. There were two experiments, an incubation study to investigate the relative efficacy of various amendments in releasing soluble P from rockphosphate and a pot culture experiment to study the comparative efficiency of rock phosphate with amendments.